2021
DOI: 10.1016/j.cbi.2021.109480
|View full text |Cite
|
Sign up to set email alerts
|

Potent toxic effects of Taroxaz-104 on the replication of SARS-CoV-2 particles

Abstract: Polyphenolics and 1,3,4-oxadiazoles are two of the most potent bioactive classes of compounds in medicinal chemistry, since both are known for their diverse pharmacological activities in humans. One of their prominent activities is the antimicrobial/antiviral activities, which are much apparent when the key functional structural moieties of both of them meet into the same compounds. The current COVID-19 pandemic motivated us to computationally screen and evaluate our library of previously-synthesized 2-(3,4,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Although proposed drugs and vaccine candidates were approved for emergency treatment of COVID-19, the FDA recommended a few drugs to help control the pandemic. But there is still a need to expand the number of potential drug candidates that could have higher efficacy and fewer side effects for the treatment of COVID-19 [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…Although proposed drugs and vaccine candidates were approved for emergency treatment of COVID-19, the FDA recommended a few drugs to help control the pandemic. But there is still a need to expand the number of potential drug candidates that could have higher efficacy and fewer side effects for the treatment of COVID-19 [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…Teriflunomide molecule has much simpler structure with lower molecular weight and volume if it is compared to the structures of both used references. The highly-balanced flexibility of the uncomplicated structure of teriflunomide is crucially needed for outstanding and perfect positioning of the drug molecule to be extremely superimposable in the active binding pocket and cavity of the COVID-19 polymerase protein (i.e., required for the extreme lock-and-key positioning) ( Rabie, 2021e ). This, in turn, results in more proper and sufficient (i.e., potent) inhibition of the replication activities mediated or controlled by the SARS-CoV-2 RdRp.…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 has sheaths that enfold around the RNA genome (virion, which is the whole virus, is round/oval, usually polymorphic, with a diameter of approximately 50–200 nm) ( Wu et al, 2020 ). Except for the promising investigational drugs, cyanorona-20, CoViTris2020, ChloViD2020, and Taroxaz-104, there is no specific and effective potent drug therapy successfully recognized for COVID-19 to date at the middle of 2021 ( Jiang et al, 2020 ; Rabie, 2021a , 2021b , 2021c , 2021d ; Rabie, 2021e ; Rabie, 2021f ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols possess a wide range of health benefits and biological activities, including antioxidant [50], antitumoral [51], anti-inflammatory [52], and antiviral properties [53], the latter of which suggests that polyphenols may be useful in the battle against multiple viruses, even SARS-CoV-2 [27,[54][55][56][57][58][59][60][61][62]. In fact, numerous studies have shown that polyphenols exhibit antiviral effects by inhibiting DNA/RNA synthesis [63][64][65][66][67]. Our previous study also demonstrated that miquelianin, a flavonol glucuronide, can compete for the binding site of dATP on HIV-1 reverse transcriptase, inhibiting the viral DNA synthesis by interacting with the last nucleotide of the RNA chain and the binding residues of DNA polymerase [68].…”
Section: Discussionmentioning
confidence: 99%